HUBUNGAN KEBIASAAN SARAPAN DAN KONSUMSI TABLET TAMBAH DARAH DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMPN 13 MATARAM - Amila Fadila, Lina Nurbaiti, Putu Aditya Wiguna (Jurnal Medika Hutama, 2024)
Anemia is a worldwide micronutrient problem. About 30% of the population worldwide is estimated to be anemic (WHO, 2018). Indonesia is one of the contributors to the high incidence of anemia in the world (WHO, 2018). The prevalence of anemia in adolescent girls in Indonesia has increased every year. Based on Riskesdas data in 2013, the prevalence of anemia in adolescent girls was 37.1% and increased to 48.9% in Riskesdas 2018. The main risk factors for the high incidence of anemia in adolescent girls are low nutrient intake and non-compliance in taking blood supplement tablets. The research method that will be used by researchers is observational analytic. The population in this study were adolescent girls in grades VII, VIII and IX at SMPN 13 Mataram with a total of 442 students. Based on the results of the chi square test on the relationship between breakfast habits and the incidence of anemia, it shows a p value = 0.010 (<0.05), which means that there is a relationship between breakfast habits and the incidence of anemia. There is a relationship between breakfast habits and consumption of blood supplement tablets with the incidence of anemia in adolescent girls at SMPN 13 Mataram.